Predation and parasitism on herbivorous insects change in opposite directions in a latitudinal gradient crossing a boreal forest zone - Zvereva Elena L; Zverev Vitali; Kozlov Mikhail V (WILEY, 2022)
The latitudinal biotic interaction hypothesis (LBIH) predicts that the strength of various biotic interactions decreases from low to high latitudes. Inconsistency between studies testing this hypothesis may result from variations among different types of interactions and among study systems. Therefore, exploration of multiple interactions within one system would help to disentangle latitudinal patterns across individual interactions and to evaluate latitudinal changes in the overall impact of enemies on prey. We tested the prediction based on the LBIH that the pressure of natural enemies on herbivorous insects decreases with increase in latitude across the boreal forest zone. We also asked whether the impacts of major groups of these enemies exhibit similar latitudinal patterns and whether these patterns are consistent across study years. In 10 forest sites located from 60 degrees N to 69 degrees N in Northern Europe, each summer, from 2016 to 2019, we measured (a) mortality of three groups of leafmining insects caused by birds, ants, parasitoids and unknown factors, (b) bird attacks on caterpillar-shaped plasticine models and (c) birch foliar damage caused by defoliators and leafminers. Latitudinal patterns in both insect herbivory on birch and top-down pressure on herbivorous insects varied considerably and inconsistently among the four study years, so that only some of the year-specific correlations with latitude were statistically significant. Nevertheless, meta-analysis combining correlations across years, preys and enemies revealed general decreases in predation by birds (on both natural and model prey) and ants, but an increase in parasitism rates, from low to high latitudes. We found that the direction of latitudinal changes in the strength of biotic interactions was interaction-specific: predation and herbivory supported LBIH, whereas parasitism exhibited an opposite trend. Consequently, the overall impact of natural enemies on herbivorous insects did not change with latitude and was therefore an unlikely reason for the poleward decrease in herbivory observed in our gradient. Considerable among-year variation in the strength of the latitudinal patterns in all the studied interactions suggests that this variation is a widespread phenomenon.